PODMIOTOWOŚĆ BEZPIECZEŃSTWA ENERGETYCZNEGO W WYBRANYCH REGIONACH POLSKI PRZY WYKORZYSTANIU ZASOBÓW GEOTERMALNYCH - Świerszcz Katarzyna; Ćwik Bogdan (2020)
The study attempts to analyse the issues that should to create the subjective of polish energy security in the context of rich geothermal resources being at the disposal of the various regions of our country. adoption of these measures allows not only to increase the diversification of sources of energy supply, but also brings significant benefits in economic, social and environmental, as well as in the areas of security and defense. This issue is presented in three aspects: • sources and geothermal energy resources in different regions of Polish; • advantages and disadvantages of using geothermal energy; • examples of the use of geothermal energy in some regions of Poland. in order to show deeper explore of the problem, it was used a research of analytical and synthetic method.